Extension education’s role towards community empowerment in Nigeria: issues, challenges and prospects - Gombe, Sani Yakubu; Suandi, Turiman; Ismail, Ismi Arif; Omar, Zoharah (Center for Promoting Ideas, 2016)
Over time extension education is supply-driven with little or no consultation with the community members, participants, clients or partners whom the innovation and other related empowerment activities is intended. The linear model of community empowerment of top-down approach has been the dominant process of holistic sustainable development in Nigeria, resulting in failed processes towards ensuring self-dependence economically, socially, psychologically and politically. Recently, community driven development (CDD) have come to be considered as most appropriate towards sustainable community empowerment. Utilization of these techniques by the extension educators was found to have increases the community members’ knowledge and ability to make their own choices and decisions on each and every developmental program and projects. Community members assumed a central role and become key players in activities that will affect their lives such as: needs assessment, planning, implementation, supervision, monitoring, and evaluation of projects. This paper examined the roles of extension education towards community empowerment in Nigeria: issues, challenges, and prospects. These issues and challenges include political system, gender, population, funding, training, and re-training, competencies, and manpower. The paper also recommends government proactive measure in terms of legislation, funding and more employment and also the communities to form self-help groups as a way of empowering themselves internally in collaboration with the extension workers working with them.